Turbulent drifts of impurity ions as an explanation for anomalous radial transport in the far-SOL of DIII-D - S.A. Zamperini; T.N. Bernard; D.L Rudakov; J.A Boedo (Nuclear Fusion)
Successful fusion reactor operation relies on minimal core contamination by impurities, otherwise too much power may be radiated and harm performance. This requires reliable predictions of impurity transport from the scrape-off layer (SOL) into the core, beyond the traditional ‘anomalous’ diffusion approach. We report a set of far-SOL tungsten transport simulations that demonstrate the role of turbulent drifts on radial impurity transport. A turbulent plasma background is simulated using the gyrokinetic SOL code Gkeyll. Tungsten ions are followed within the plasma background using only their drifts. We find that tungsten tends to travel radially outwards with velocities between v _r = 300–1200 m s ^−1 primarily due to polarization drift. We also extract an anomalous radial diffusion coefficient that varies from $D_{\text{r}}^{{\text{anom}}}$ = 5–20 m ^2 s ^−1 . These results are compared to and agree with previous interpretive modeling results. We also show how the turbulent polarization drift can transport some tungsten ions from the wall inwards with effective pinch velocities up to 10 000 m s ^−1 . We conclude that turbulent drifts are a likely explanation for historically anomalous radial impurity transport.